1995
DOI: 10.1523/jneurosci.15-02-01463.1995
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of connectivity in the cat cerebral cortex

Abstract: The mammalian cerebral cortex is innervated by a large number of corticocortical connections. The number of connections makes it difficult to understand the organization of the cortical network. Nonetheless, conclusions about the organization of cortical systems drawn from examining connectional data have often been made in a speculative and informal manner, unsupported by any analytic treatment. Recently, progress has been made toward more systematic ways of extracting organizing principles from data on the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
476
1
2

Year Published

1998
1998
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 513 publications
(511 citation statements)
references
References 138 publications
(207 reference statements)
32
476
1
2
Order By: Relevance
“…Most structural analyses of brain networks have been carried out on datasets describing the large-scale connection patterns of the cerebral cortex of rat [20], cat [21,22], and monkey [23] -structural connection data for the human brain is largely missing [24]. These analyses have revealed several organizational principles expressed within structural brain networks.…”
Section: Structural Organization Of Cortical Networkmentioning
confidence: 99%
“…Most structural analyses of brain networks have been carried out on datasets describing the large-scale connection patterns of the cerebral cortex of rat [20], cat [21,22], and monkey [23] -structural connection data for the human brain is largely missing [24]. These analyses have revealed several organizational principles expressed within structural brain networks.…”
Section: Structural Organization Of Cortical Networkmentioning
confidence: 99%
“…Similarly, the jingle in the back of the mind might be P-conscious without being A-conscious. Blakemore, and Young (1995;Scannell et al, 1999) have performed detailed analyses of cortical connectivity in the cat and found that the cortical regions can be divided into four highly interconnected groups: the visual system, the auditory system, the somatosensory-motor system, and the frontal-hippocampal system. Based on the previous discussion, we can postulate that the establishment of focal awareness requires involvement of the frontal-hippocampal system.…”
Section: ''Background'' Mental Representationsmentioning
confidence: 99%
“…Such a bifurcation can save Ϸ10% of the corresponding length of two separate connections (4,14). However, cerebral connection compendia only describe links between pairs of areas (15,16); they therefore cannot systematically represent these branchings, and so remain inaccurate as a basis for computing wire costs. Is optimization still discernable through so many barriers?…”
mentioning
confidence: 99%